Assessment of the students’ expectations and perception regarding the development of the competences in industrial engineering course - Veraldo, Lucio Garcia [UNESP] (2018)
The challenges of higher education institutions in analyzing the development of egress skills during undergraduate course become more important in preparing for the job market. Applying assessments that characterize the skills of these students is critical to preparing them professionally, after all, it takes much more than the knowledge gained. The purpose of this article is to present the expectations and perceptions of the students of the Industrial Engineering course in the development of their abilities in the accomplishment of an interdisciplinary project. Soon after the presentation of the project to be developed by the teams, the students evaluated their expectations of personal and interpersonal skills development. At the end of the semester, students assessed their perceptions of the development of these skills through the interdisciplinary project. The assessments were carried out by on the scale students who started from exposure and experimentation to the innovation and leadership of the developed project.